Findings from the School-Based Theatrical Performance Walk In Our Shoes - Wong, Eunice C. (Rand Health Q, 2014)
This article examines the effects of a school-based theatrical performance, Walk In Our Shoes, designed to educate youth about and reduce stigma and discrimination toward mental illness.